2016
DOI: 10.1159/000447515
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Central Precocious Puberty Development Caused by an <b><i>MKRN3</i></b> Gene Mutation: A Prismatic Case

Abstract: Background: Loss-of-function mutations in the imprinted gene MKRN3 represent the most common known genetic defects associated with central precocious puberty (CPP). Methods: We report the first case of a girl carrying an MKRN3 mutation detected in childhood and followed until the development of pubertal signs. Results: The girl was screened at the age of 4 years because of a positive family history; her sister had developed CPP at 6 years of age and was found to harbor the MKRN3 p.Pro161Argfs*16 mutation, inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…MKRN3 defects were described in 89 patients (76 girls and 13 boys) with CPP from 17 countries: Argentina [15], Belgium [4], Brazil [4, 5, 15, 16, 31], Bulgaria [20], Cyprus [25, 26], Denmark [28], France [7], Germany [9], Greece [6], Israel [8], Italy [7, 10, 19, 27], Japan [14], Korea [12], Spain [13], Taiwan [29], Turkey [11, 30], and United States of America [4]. Eighty-eight patients harbored mutations in the coding sequence and one exhibited a deletion in the promoter region of the gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MKRN3 defects were described in 89 patients (76 girls and 13 boys) with CPP from 17 countries: Argentina [15], Belgium [4], Brazil [4, 5, 15, 16, 31], Bulgaria [20], Cyprus [25, 26], Denmark [28], France [7], Germany [9], Greece [6], Israel [8], Italy [7, 10, 19, 27], Japan [14], Korea [12], Spain [13], Taiwan [29], Turkey [11, 30], and United States of America [4]. Eighty-eight patients harbored mutations in the coding sequence and one exhibited a deletion in the promoter region of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…Younger carriers of MKRN3 mutations identified by family screening before the development of pubertal signs have also been described [7, 11], and their clinical follow-up are still not known. Stecchini et al reported a case of a girl identified as a carrier of MKRN3 mutation at the age of 4 because of a positive family history, who was diagnosed with CPP at the age of 6.7 years [16].…”
Section: Resultsmentioning
confidence: 99%
“…2A), was reported in 2013 as the first gene in which loss-of-function mutations were associated with CPP, with variants initially identified by exome sequencing in five families (27). Multiple novel variants, including frameshift, nonsense, and missense mutations, in MKRN3 across various families, ethnicities and geographical regions have now been reported (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50). Mutations in MKRN3 are now the most common known genetic etiology of CPP and are more common in familial CPP (33-46% of cases) compared to sporadic CPP (3.9% of cases) (28).…”
Section: Mkrn3mentioning
confidence: 99%
“…18 Subsequently, mutations in MKRN3 have been described in many additional patients with CPP throughout the world. [21][22][23][24][25][26][27][28][29][30][31][32] For a recent systematic review and meta-analysis of the MKRN3 mutations identified in patients with CPP to date, see the study by Valadares et al 33 Precocious puberty is clinically defined by the development of secondary sexual characteristics before the age of 8 years in girls and 9 years in boys, which corresponds to 2.5 to 3 standard deviations below the mean age of puberty onset, as defined by population studies. 34 Early age of puberty has been associated with many deleterious health effects such as cancer, cardiovascular disease, and metabolic and behavioral disorders.…”
Section: Mkrn3 Mutations In Central Precocious Pubertymentioning
confidence: 99%